Les-Be-Queer: A Historical Exploration of Queer People at Stellenbosch University, c. 1987-2024 - Le Roux, Jesse Baronne (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.